Dixon’s Framework Model of Think Verbs in English and Wawonii Language - Mirdad Mirdad; Harlina Sahib; Karmila Mokoginta (ELS Journal on Interdisciplinary Studies in Humanities, 2022)
The aim of the current study is to examine the employment of the Think verbs in English and Wawonii language, employing Dixon’s framework model of semantic and grammatical relations. In analyzing the phenomenon of the Think verbs in English and Wawonii, this study uses a descriptive qualitative methodology. The data for English is taken from a corpus of contemporary American English (COCA), including the definition of the conceptual meaning of the Think verbs in a thesaurus dictionary and Journals. The Wawonii language data is obtained through depth online interviews. The participants are 10 indigenous Wawonii people in Kabupaten Konawe Kepulauan, Southeast Sulawesi, Indonesia. Several procedures are applied to analyze the data; first, the data for the English language from COCA is constructed with the data of the Wawonii language that had been collected. Then, presenting both of the data based on Dixon’s framework model. The final step is concluding the data reflecting the main point of the analysis relying on Dixon’s framework model. This study discovered that (1) There are three Thinking verbs of the Think subtype in English they are Think of, Think over, and Think about, while in the Wawonii language, there are six Think verbs; Mepikiri Kanaampe, Pepikiri kida, Tepikiri kio, Kohawa-hawa Kanaampe, Momaana, and Mompatudu. (2) Dixon’s five framework model of Think verbs is employed in both languages. This study contributes to the language and society to enrich a variety of works of literature that can be used to learn English and the Wawonii language.